Translating Transgressions in Olga Tokarczuk’s Drive Your Plow Over the Bones of the Dead: - Joutha Monisha (Crossings)
Drive Your Plow Over the Bones of the Dead is a 2009 murder-mystery novel written by Nobel laureate Olga Tokarczuk and translated to english by Antonia Llyod-Jones in 2018. It follows aging eccentric Janina Duszejko as a series of murders take place in the plateau where she lives. Under the parable-esque, whodunit nature of the novel, Tokarczuk explores the theme of transgressions in the light of animal rights activism. This essay is an investigation into the contrasting ideas highlighted by the authorial voice and the persepective held by the protagonist’s in the light of affect theory and Tokarczuck’s own conception of a tender narrator. I argue that Tokarczuk highlights the ambiguity of borders and boundaries in the narration to explore the implications of Duszejko’s transgression of societal law and constrcuting herself as a tool by which animals inact their vengence.